On action of outer derivations on nilpotent ideals of Lie algebras - Maksimenko, D.V. (Algebra and Discrete Mathematics, 2009)
Action of outer derivations on nilpotent ideals of Lie algebras are considered. It is shown that for a nilpotent ideal I of a Lie algebra L over a field F the ideal I+D(I) is nilpotent, provided that charF=0 or I nilpotent of nilpotency class less than p−1, where p=charF. In particular, the sum N(L) of all nilpotent ideals of a Lie algebra L is a characteristic ideal, if charF=0 or N(L) is nilpotent of class less than p−1, where p=charF.